The validity and reliability of Systemic Lupus Erythematosus Quality of Life Questionnaire (L-QoL) in a Turkish population - ŞANAL TOPRAK, CANAN; DURUÖZ, MEHMET TUNCAY (SAGE PUBLICATIONS LTD, 2017)
Background Systemic lupus erythematosus (SLE) may have a profound impact on quality of life. There is increasing interest in measuring quality of life in lupus patients. The purpose of this study was to investigate the validity and reliability of SLE Quality of Life Questionnaire (L-QoL) in Turkish SLE patients. Methods SLE according to 2012 Systemic Lupus International Collaborating Clinics Classification Criteria were recruited into the study. Demographic data, clinical parameters and disease activity measured with the Systemic Lupus Erythematosus Disease Activity Index-2000 (SLEDAI-2K); were noted. Nottingham Health Profile and Health Assessment Questionnaire were filled out in addition to the Turkish L-QoL (LQoL-TR). Internal consistency, test-retest reliability, and convergent and discriminant validity were evaluated. Results The mean age of participants was 43.5514.33 years and the mean disease duration was 89.8 +/- 92.1 months. The patients filled out LQoL-TR in 2.5min. Strong correlation of LQoL-TR with all subgroups of the Nottingham Health Profile and the Health Assessment Questionnaire were established showing the convergent validity. The highest correlation was demonstrated with emotional reactions (rho=0.72) and sleep component (rho=0.65) of the Nottingham Health Profile scale (p<0.0001). Its poor and not significant correlation with nonfunctional parameters (age, disease duration, perceived general health, SLEDAI-2K) showed its discriminative properties. LQoL-TR demonstrated good internal reliability with a Cronbach's of 0.93 and test-retest reliability with intraclass correlation coefficient of 0.87. Conclusion The LQoL-TR is a practical and useful tool which demonstrates good validity and reliability.
Keywords: Disease specific outcome measure; L-QoL; systemic lupus erythematosus; validation; HEALTH-ASSESSMENT QUESTIONNAIRE; CROSS-CULTURAL ADAPTATION; DISEASE-ACTIVITY; SLEEP DISTURBANCES; VALIDATION; VERSION; PREVALENCE; DIMENSIONS; DISABILITY; GUIDELINES